The 'Feminine Revolution in Mining': a critique - Pini, Barbara; Mayes, Robyn (Routledge, 2010)
This paper presents an analysis of media reports of Australian women in mine management. It argues that a dominant storyline in the texts is one of gender change; in fact, a "feminine revolution" is said to have occurred in the mining industry andcorporate Australia more generally. Despite this celebratory and transformative discoursethe female mine managers interviewed in the media texts seek to distance themselves from women/female identity/femininity and take up a script of gender neutrality. It is demonstrated, however, that that this script is saturated with the assumptions and definitions of managerial masculinity.